A web-based information management system for the University of the Philippines Mindanao Alumni Association (UPMIN AA) Clady Mae Durens Ceniza. - Ceniza, Clady Mae Durens (2011)
Universities recognize alumni as main supporters of a range of programs and services. After graduating from UP Mindanao, a stress to access the alumni worldwide is essential in this field attaching volumes of information. The system is designed for two end-users: the administrator and alumni users. With the web-based information management system the administrator may no longer manually encode each detail to a spreadsheet file and the alumni may load entries of information along with the interaction to the university. The system offers the following services to the end-users: to manage all profile information, job postings, reunion announcements, university activities and events, alumni workshops, donations and awards, and even upload and download files online exclusively for registered users. This is also a convenient way of keeping records and organizing one's information for both the administrator and alumni end-users. For further extensions and improvements, the system may be studied by Computer Science enthusiasts for better output. The information acquired in this system is confidential so an enhanced security measures should be done over the data obtained. The web-based information management system can also be improved by integrating this to CSRS that takes control of the authentication of the valid alumni in the university. It could also be enhanced by providing features where the user can be notified through e-mail for urgent announcements and can choose options to subscribe for daily updates from the university via a newsletter. It is recommended to utilize the Javascript language such as jQuery scripting with an Ajax approach for better throughput. Adding more related features with the recommendations asserted might evolve the system itself into a more efficient and helpful application system in the future.